Some International Aspects of British Cyclical Fluctuations, 1870-1913 - Pesmazoglu, J. S. (Review of Economic Studies, 1949)
Journal Article Some International Aspects of British Cyclical Fluctuations, 1870–1913 Get access J. S. Pesmazoglu J. S. Pesmazoglu Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 16, Issue 3, 1949, Pages 117–143, https://doi.org/10.2307/2295915 Published: 01 January 1949